Insight into the Endocrine System and the Immune System: A Review of the Inflammatory Role of Prolactin in Rheumatoid Arthritis and Psoriatic Arthritis - Tang, Man W.; Garcia, Samuel; Gerlag, Danielle M.; Tak, Paul P.; Reedquist, Kris A. (Frontiers in Immunology, 2017)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects females three times more frequently than males. A potential role for hormones, such as prolactin (PRL), may in part explain this phenomenon. The risk of developing RA is increased in women who are lactating after the first pregnancy, which might be related to breastfeeding and the release of PRL. Other studies found a protective effect of PRL on RA development. Some studies have reported that hyperprolactinemia is more common in RA and serum PRL levels are correlated with several disease parameters, although others could not confirm these findings. Overall the plasma PRL levels are on average not elevated in RA.. Previously, a small number of open label clinical trials using bromocriptine, which indirectly decreases PRL levels, were performed in RA patients and showed clinical benefit, although others found the opposite effect. Locally produced PRL at the site of inflammation may have a crucial role in RA as well, as it has been shown that PRL can be produced by synovial macrophages. Locally produced PRL has both pro-inflammatory and anti-inflammatory effects in arthritis. Psoriatic arthritis (PsA) is also an autoinflammatory disease, in which the PRLR is also expressed in macrophages. The aim of this review is to provide an overview of the potential role of PRL signalling in inflammatory joint diseases (RA and PsA) and its potential as a therapeutic target.